Ningxiang pig-derived lactobacillus reuteri modulates host intramuscular fat deposition via branched-chain amino acid metabolism - Mei Yang; Qian Xie; Jing Wang; Andong Zha; Jiashun Chen; Qian Jiang; Meng Kang; Qiuchun Deng; Yulong Yin; Bie Tan (Microbiome)
Abstract Background Gut microbiota has been extensively demonstrated to modulate host lipid metabolism. Higher intramuscular fat (IMF) accumulation in Chinese indigenous breed pigs is associated with their special gut microbiota structure. However, the specific microbes and metabolic pathways responsible for lipid deposition are still poorly understood. Results In the present study, a comparative analysis of the gut microbiota and metabolome in obese Ningxiang (NX) pigs and lean Duroc × Landrace × Yorkshire (DLY) pigs was conducted. The results revealed a higher abundance of gut lactobacilli and a correlation of branched-chain amino acid (BCAA) metabolism pathway in NX pigs. We proceeded to verify the roles of various lactobacilli strains originating from NX pigs in BCAA metabolism and lipids deposition in SD rats. We demonstrated that L. reuteri is a fundamental species responsible for modulating lipid deposition in NX pigs and that increased circulating levels of BCAA are positively linked to greater lipid deposition. Additionally, it has been verified that L. reuteri originating from NX pigs has the ability to improve BCAA synthesis in the gut and enhance IMF content in lean DLY pigs. The expression of genes related to lipid synthesis was also significantly upregulated. Conclusions Taken together, our results imply that NX pig-derived L. reuteri regulates BCAA metabolism and plays a potential role in improving the meat quality of lean pig breeds through modulation of host intramuscular lipid deposition. The results provide a new strategy for improving the meat quality of commercial pigs by influencing host metabolism through supplementing dietary additives. Video Abstract